Translating Maternal Violence : The Discursive Construction of Maternal Filicide in 1970s Japan - Castellini, Alessandro (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book provides the first full-length, English-language investigation of the multiple and often contradictory ways in which mothers who kill their children were portrayed in 1970s Japan. It offers a snapshot of a historical and social moment when motherhood was being renegotiated, and maternal violence was disrupting norms of acceptable maternal behaviour. Drawing on a wide range of original archival materials, it explores three discursive sites where the image of the murderous mother assumed a distinctive visibility: media coverage of cases of maternal filicide; the rhetoric of a newly emerging women's liberation movement known as ūman ribu; and fictional works by the Japanese writer Takahashi Takako. Using translation as a theoretical tool to decentre the West as the origin of (feminist) theorizations of the maternal, it enables a transnational dialogue for imagining mothers' potential for violence. This thought-provoking work will appeal to scholars of feminist theory, cultural studies and Japanese studies.- Resumé vydavatel
Keywords: Takahashi, Takako -- 1932-2013; násilí na dětech -- 1971-1980 -- Japonsko; kriminalita -- sociologické aspekty -- 1971-1980 -- Japonsko; mateřství -- dějiny -- 20. století -- Japonsko; kulturální studia; feminismus; japonská literatura; child abuse -- 1971-1980 -- Japan; crime -- sociological aspects -- 1971-1980 -- Japan; motherhood -- history -- 20th century -- Japan; cultural studies; feminism; Japanese literature; elektronické knihy; monografie; electronic books; monographs